Knowing Through Consulting in Action Meta-consulting Knowledge Creation Pathways - CIAMPI, Francesco (Studi e saggi, 2017)
Management consulting firms are often discussed as being the firms whose core product is knowledge itself. However, despite the fact that consulting firms are generally aware of the value of knowledge for their own organizations and for their clients, the empirical evidence shows that even today the (economic and, above all, cognitive) value-creation potential related to the transition from consulting approaches geared to the transfer of "best practices" (consultant as expert) to consulting approaches geared to the cooperative creation of new knowledge and managerial capabilities (consultant as a facilitator of new managerial knowledge and capabilities creation processes) is rarely consciously perceived and, consequently, is not adequately planned for and exploited. This book interprets management consulting from a knowledge perspective, and proposes a general conceptual framework for investigating and interpreting that potential.